Theoretical Study of the Structural and Electronic Properties of NIPAM Polymer Dosimetry Gel - Swait S. Mohammed; Israa F. Al-sharuee; Akram Mohammed Ali; Adil Elrayah (Al-Mustansiriyah Journal of Science)
Background: Gel dosimeters consist of two types: Frick and Polymer, with compounds that are highly reactive to radiation. Objective: The difference in energy between the Highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) was investigated. Methods: An examination of the structure of a dosimetry gel polymer of type N- sopropylacrylamide (NIPAM) was carried out with the assistance of the Gaussian 09 software, the Fourier Transform Infrared Spectrometer (FTIR), the proton and carbon nuclear magnetic resonance (H NMR-C NMR), and the ultraviolet-visible spectroscopy (UV-vis) approach were used. The molecular geometry was determined using density functional theory (DFT) (B3LYP) and computational means. Subsequently, this molecule’s vibrational frequencies and electrical characteristics were examined, with the ground state represented by the 6-31G basis. The computations of the structure, as well as the vibrational frequencies and chemical shift, demonstrated a satisfactory theoretical approximation. Results: Based on the findings, it has been shown that NIPAM has a high-water solubility and is of great assistance in the process of introducing a powerful polar amide group into a hydrophobic polymer via the use of suspension or emulsion polymerization, and strong coupling effect (interaction of magnetic fields) between the hydrogen atoms and the deformation. Conclusions: The atoms within the structure, the molecule is highly reactive, the computed results demonstrated the accuracy of the theoretical approximation despite these discrepancies.